Cherry laurel fruit extract counters dimethoate-induced reproductive impairment and testicular apoptosis - Bakir, Elcin; Sariozkan, Serpil; Endirlik, Burcu Unlu; Kilic, Ayse Baldemir; Yay, Arzu Hanim; Tan, Fazile Canturk; Turk, Gaffari (Sciendo, 2020)
Dimethoate is an organophosphorus pesticide used against agricultural insects, which causes oxidative stress and damage in many organs, including the reproductive ones. Cherry laurel (Laurocerasus officinalis Roem.) fruit is rich in vitamins and phenolic compounds with antioxidant effect. The aim of this study was to investigate how effective its extract would be against dimethoate-induced testis and sperm damage in rats. Sixty animals were divided in six groups of 10. Group 1 (control) received only 1 mL of saline (0.9 % NaCl). Group 2 received 7 mg/kg of dimethoate in 1 mL of saline. Group 3 received 4 mg/kg of extract in 1 mL of saline. Group 4 received the extract 30 min before dimethoate administration. Group 5 received vitamin C (positive control, 100 mg/kg in 1 mL of saline) 30 min before dimethoate administration. Group 6 received only dimethoate for the first four weeks and then a combination of dimethoate and extract for another four weeks. All doses were administered daily by oral gavage. After eight weeks of treatment, the rats were euthanised and their reproductive organs removed. We took their body and reproductive organ weights and evaluated testicular oxidative stress, semen characteristics, sperm DNA damage, testicular apoptosis, and histopathological changes. Dimethoate significantly decreased body and reproductive organ weights, sperm motility and concentration, testicular superoxide dismutase, and glutathione-peroxidase activities and significantly increased lipid peroxidation, abnormal sperm rate, sperm DNA damage, testicular apoptosis, and caused histopathological lesions. Cherry laurel extract significantly countered many dimethoate-induced adverse effects, both as pre- and post-treatment, including reproductive organ weight, semen parameters, oxidant-antioxidant balance, sperm DNA integrity, testicular apoptosis, and histological structure. Our findings clearly suggest that the beneficial effects of the extract are associated with countering oxidative stress, lipid peroxidation in particular.
Keywords: Laurocerasus officinalis Roem.; organophosphorus pesticide; oxidative stress; sperm DNA damage; testis